2012
DOI: 10.2903/j.efsa.2012.2847
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the substantiation of health claims related to soy isoflavones and maintenance of bone mineral density (ID 1655) and reduction of vasomotor symptoms associated with menopause (ID 1654, 1704, 2140, 3093, 3154, 3590) (further assessmen

Abstract: Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to provide a scientific opinion on health claims pursuant to Article 13 of Regulation (EC) No 1924/2006 in the framework of further assessment related to soy isoflavones and maintenance of bone mineral density and reduction of vasomotor symptoms associated with menopause. The food constituent that is the subject of the claim, soy isoflavones, is sufficiently characterised. The claimed effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 80 publications
0
3
0
1
Order By: Relevance
“…The European Food Safety Authority has evaluated the effects of isoflavones on the risk of cardiovascular disease, with a focus on the effects on lipid profile. (23) Several previous studies have investigated the important clinical effects of isoflavones on the decreases in total cholesterol, LDL cholesterol, and TAG levels and on the increase in HDL cholesterol levels. These studies that were reported in the last ten years failed to demonstrate that isoflavones exert significant clinical effects, and failed to find the active isoflavone compounds that play a role in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The European Food Safety Authority has evaluated the effects of isoflavones on the risk of cardiovascular disease, with a focus on the effects on lipid profile. (23) Several previous studies have investigated the important clinical effects of isoflavones on the decreases in total cholesterol, LDL cholesterol, and TAG levels and on the increase in HDL cholesterol levels. These studies that were reported in the last ten years failed to demonstrate that isoflavones exert significant clinical effects, and failed to find the active isoflavone compounds that play a role in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest high intakes of isoflavones to be associated with fewer and less intense menopause symptoms, and a reduced incidence of hormone-dependent and aging-associated diseases such as osteoporosis, cardiovascular diseases and cancer [1]. Although there is a growing body of scientific evidence showing beneficial effects in counteracting symptoms such as hot flushes and vasomotor reactions in menopausal women [2], the European Food Safety Authority (EFSA) has recently refuted health claims about the role of isoflavones in body functions [3]. This may be so because the functionality of isoflavones depends on their bioavailability and their conversion into (more) active metabolites within the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Sur 1 colonne près de son appel TEG1 Bien que de nombreuses études soient publiées sur les isoflavones de soja, leurs méthodologies et résultats ne permettent pas d'affirmer qu'ils permettent de diminuer les bouffées de chaleur [26][27][28]. Ils pourraient empêcher l'ostéoporose mais se limiteraient à maintenir la densité minérale et non à prévenir les risques de fractures.…”
Section: Encadré 2 Définition Des Phyto-estrogènesunclassified